The girl from the other side : Siúil, a Rún. Vol. 1 - Nagame; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, LLC, 2017)
"In a land far away, there were two kingdoms: the Outside, where twisted beasts roamed that could curse with a touch, and the Inside, where humans lived in safety and peace. The girl and the beast should never have met, but when they do, a quiet fairytale begins"--Provided by publisher.